Hsichengia: A 4,6-connected trigonal structural pattern in space group P3m1 - Bucknum, Michael J. (2009)
A novel 4,6-connected network, called Hsichengia, is described. The novel network lies in the trigonal space group P3m1 (no. 156), with a = b = 3.447 A and c = 12.948 A; these lattice parameters were derived assuming Fe-S composition. It implies a binary AB2 stoichiometry in which the 6-connected A (Fe) atoms have octahedral configuration, and the 4-connected B (S) atoms have tetrahedral configuration. The Hsichengia network seems to be very closely related to the layered MoS2 structure-type, in which puckered MoS2 layers composed of octahedral Mo centers and trigonal-pyramidal S centers are held together by weak van der Waals forces normal to the a and b directions where the MoS2 layers extend. Thus the Hsichengia network can be generated from the MoS2 lattice by the formation of disulfide (S-S) bridges between particular layers, thereby creating a 3-dimensional network from a 2-dimensional layered structure, so that the S atoms are transformed from 3-connected trigonal-pyramidal coordination into fully 4-connected tetrahedral coordination. The Wells point symbol for the Hsichengia network is given by (4666)(4363)2, and it is thus seen to have the translated Schlafli symbol given as (5, 42/3). The latter is identical to that intrinsic to the well-known mineral structure of the pyrite network, FeS2, with the corresponding Wells point symbol (512)(56)2. Therefore, the Hsichengia network may be regarded as a topological isomer of the pyrite network, where topological isomerism is defined as occurring between unique networks possessing the same Schlafli symbol. Phase transformation between the two topological isomers is possible.